2013
DOI: 10.1073/pnas.1318547111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intramitochondrial ATP levels identifies G0/G1 switch gene 2 as a positive regulator of oxidative phosphorylation

Abstract: The oxidative phosphorylation (OXPHOS) system generates most of the ATP in respiring cells. ATP-depleting conditions, such as hypoxia, trigger responses that promote ATP production. However, how OXPHOS is regulated during hypoxia has yet to be elucidated. In this study, selective measurement of intramitochondrial ATP levels identified the hypoxia-inducible protein G0/G1 switch gene 2 (G0s2) as a positive regulator of OXPHOS. A mitochondria-targeted, FRET-based ATP biosensor enabled us to assess OXPHOS activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 39 publications
4
89
1
Order By: Relevance
“…FRET-based measurement of mitochondrial ATP concentration in cardiomyocytes was measured as previously described (8,33). Briefly, FRET signal was measured in cardiomyocytes infected with adenovirus encoding mit-AT1.03 with an Olympus IX-81 inverted fluorescence microscope (Olympus) using a PL APO 60×, 1.35 N.A., oil immersion objective lens (Olympus).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRET-based measurement of mitochondrial ATP concentration in cardiomyocytes was measured as previously described (8,33). Briefly, FRET signal was measured in cardiomyocytes infected with adenovirus encoding mit-AT1.03 with an Olympus IX-81 inverted fluorescence microscope (Olympus) using a PL APO 60×, 1.35 N.A., oil immersion objective lens (Olympus).…”
Section: Methodsmentioning
confidence: 99%
“…Several proteins involved in oxygen supply or metabolism are transcriptionally regulated by intracellular oxygen concentration: vascular endothelial growth factor (VEGF) (6), erythropoietin (EPO) (7), and G0/G1 switch gene 2 (G0s2) for F o F 1 -ATP synthase, as we recently revealed (8). Because CcO is the only enzyme in the body that can use oxygen for energy transduction, it has been suggested that the regulatory mechanism of CcO is dependent on oxygen concentration (9-12); however, this has yet to be demonstrated.…”
mentioning
confidence: 99%
“…G0S2 is an inhibitor of adipose triglyceride lipase and decreases lipolysis [14][15][16][17] . G0S2 is a positive regulator of oxidative phosphorylation [18] . G0S2 was upregulated in inflammatory processes, was involved in T cell quiescence, and inhibited proliferation of T cells.…”
Section: Var1mentioning
confidence: 99%
“…This could be of great importance when investigating composite parts of a larger dynamical system, and seeking to identify causal relationships between observed oscillations. For example, recent advances in cellular imaging are providing the means to observe the dynamics of individual cellular processes in different cellular compartments [34]. Applying inverse approach methods for the detection of chronotaxicity to these dynamics could provide valuable information on the current state of the cell.…”
Section: Numerical Simulationsmentioning
confidence: 99%